Disposition of oral delta-9 tetrahydrocannabinol (THC) in children receiving cannabis extracts for epilepsy - Wang, George Sam; Bourne, David W A; Klawitter, Jost; Sempio, Cristina; Chapman, Kevin; Knupp, Kelly; Wempe, Michael F.; Borgelt, Laura; Christians, Uwe; Heard, Kennon; Bajaj, Lalit (Clinical toxicology (Philadelphia, Pa.), 2020)
Introduction: Although over half of US states have legalized marijuana for medical indications, there is limited research in use in the pediatric population. The objective was to evaluate the disposition of oral tetrahydrocannabinol (THC) in children receiving cannabis extracts for pediatric epilepsy. Methods: Prospective, observational study, evaluating the disposition of oral THC in children receiving cannabis extracts. Subjects were less than 18 years of age, receiving oral cannabis for pediatric epilepsy. Subjects included in the study had at least 2 detectable THC and related metabolite plasma concentrations during serial blood draw over a 10-12 h study period. Results: Nine subjects with a median age of 11 years (IQR 4.75) were included in the study, with oral doses ranging from 0.02 mg/kg to 1.59 mg/kg. Peak plasma concentrations (0.8 to 3.6 ng/ml) in most patients were achieved within 2 hours, while acute phase elimination half-life ranged from 1 to 5 hours. THC-COOH and glucuronide remained elevated through the study period. There was significant variation between the dose ingested and peak concentrations (R 2 = 0.05). Conclusion: In pediatric patients receiving oral THC cannabis extracts, mean time to peak plasma concentrations was 2-7 hours, while mean acute phase elimination half-life was 4.0 hours. THC-COOH and THC-COOH glucuronide metabolites persisted throughout the 10-12 hour study period. Large variation and no correlation was noted between dose of THC by weight and peak concentrations, suggesting variation of bioavailability amongst pediatric population or inaccurate reporting of THC contents.